1979
DOI: 10.1111/j.1365-2265.1979.tb02106.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Functioning Adrenocortico‐myelolipoma in Longstanding Nelson's Syndrome

Abstract: A 26-year-old man with the Nelson's syndrome is described, in whom an abdominal tumour developed, accompanied by recurrent Cushing's syndrome 11 years after total adrenalectomy. Upon removal the tumour was a myelolipoma containing islands of adrenocortical-like elements. On incubation of the tumour with radioactive precursors, its capacity to produce cortisol in vitro was shown. The name adrenocortico-myelolipoma is suggested for this tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…A growing body of evidence indicates that ACTH has a role of ACTH in the development of adrenal tumors. A review of the literature reveals the relative frequency of myelolipomas in patients with excessive ACTH secretion, such as in congenital adrenal hyperplasia [3,4,9,25], Nelson's syndrome [18,21], and Addison's disease [2]. To date, approximately 20 cases of myelolipoma with congenital adrenal hyperplasia have been reported, approximately half of which are bilateral, and the left side tumor is usually larger than the right side tumor, probably due to anatomic features (Table 1) [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence indicates that ACTH has a role of ACTH in the development of adrenal tumors. A review of the literature reveals the relative frequency of myelolipomas in patients with excessive ACTH secretion, such as in congenital adrenal hyperplasia [3,4,9,25], Nelson's syndrome [18,21], and Addison's disease [2]. To date, approximately 20 cases of myelolipoma with congenital adrenal hyperplasia have been reported, approximately half of which are bilateral, and the left side tumor is usually larger than the right side tumor, probably due to anatomic features (Table 1) [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal myelolipomas sometimes arise in patients with endocrine disorders that cause adrenocorticotropic hormone (ACTH) hypersecretion, such as congenital adrenal hyperplasia. Although the pathogenesis of myelolipoma is unclear, prolonged stimulation of the adrenal cortex with high levels of ACTH or subsequent adrenal androgens may have a causative role in myelolipoma associated with congenital adrenal hyperplasia [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], Cushing's disease [18][19][20], Nelson's syndrome [21], and Addison's disease [2]. In this paper, we report a case of myelolipoma in a patient with congenital adrenal hyperplasia due to 21-hydroxylase deficiency, whose glucocorticoid replacement therapy was poorly controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenal myelolipoma has also been associated with endocrine disorders, other than congenital adrenal hyperplasia such as Cushing syndrome, and chronic stressful conditions such as obesity, diabetes mellitus, hypertension, chronic inflammatory processes and even malignancy (19,(47)(48)(49)(50)(51)(52)(53)(54). A review by Hisamatsu et al reported 26 cases of myelolipomas associated with endocrine dysfunction (16).…”
Section: Discussionmentioning
confidence: 97%
“…Another rare complication of ectopic adrenal tissue is the possible arising of a neoplasm such as neuroblastoma (usually malignant), myelolipomas and oncocytomas [2,5,8,9]. Even testicular tumours are described as presumably originating from adrenal cells [5].…”
Section: Discussionmentioning
confidence: 98%